Analisis Efektivitas LinkedIn dalam Memenuhi Kebutuhan Informasi Lowongan Kerja pada Lulusan Baru UNSIKA 2024 - atallah atallah; Weni A. Arindawati; Ema Ema (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study aims to explore the effectiveness of using LinkedIn in fulfilling job vacancy information needs among fresh graduates of Universitas Singaperbangsa Karawang (UNSIKA) in 2024. The background of this research is the high unemployment rate, particularly with 452,713 S1-S3 graduates still jobless (BPS, 2024). This study employs a quantitative approach, using Uses and Gratifications theory as the primary framework, supported by the concept of New Media as a complement. The independent variable, LinkedIn's effectiveness, is measured through the sub-variables of Context, Communication, Collaboration, and Connection. Meanwhile, the dependent variable, information needs, includes cognitive, affective, personal integration, social integration, and tension release indicators as defined by Elihu Katz, Jay G. Blumler, and Michael Gurevitch. The population consists of 3,059 fresh graduates, with a sample of 97 respondents selected using the Slovin formula and purposive sampling. Data were collected through an online questionnaire and analyzed using SPSS. The findings show that the utilization of the Context and Connection features on LinkedIn has a significant contribution in meeting the information needs of fresh graduates from UNSIKA, particularly in the cognitive and social integration aspects. In contrast, the Communication and Collaboration features did not have a significant effect. This research concludes that LinkedIn is effective for fresh graduates, with the optimization of the Context and Connection features, which can support job search strategies in the digital era.